Catheter Ablation of Atrial Arrhythmias After Cardiac Transplantation: Findings at EP Study Utility of 3‐D Mapping and Outcomes. (6th February 2013) - NOF, EYAL; STEVENSON, WILLIAM G.; EPSTEIN, LAURENCE M.; TEDROW, USHA B.; KOPLAN, BRUCE A.
Catheter Ablation of Atrial Arrhythmias Background Management of atrial arrhythmias (AA) in orthotopic heart transplant (OHT) patients is challenging. Objective The purpose of this study was to define the mechanisms of these arrhythmias and to evaluate the role of ablation. Methods Patients with OHT referred for ablation of AA from 1999 to 2011 were included (n = 15). Entrainment and anatomic 3‐D mapping were utilized to identify AA mechanism and guide ablation. Results The median time from OHT to ablation was 8 years (range: 1 month–16 years). AA types included 1 (7%) AVNRT, 5 (33%) cavotricuspid isthmus (CTI) dependent donor atrial flutter (AFl), 3 (20%) non‐CTI‐dependent donor AFL (n = 3), focal atrial tachycardia (AT) (n = 2) and in 4 (27%) recipient to donor atria conduction (RDC) that involved the right atrial anastomosis in 3 and left atrial anastamosis in 1 patient. In RDC tachycardia, ablation was performed at the site of earliest donor atrial activation on the suture line. AA in the recipient atria were not targeted. This resulted in acute success in all cases. In most patients 12/15 (80%) only right atrial ablation was necessary. Regardless of surgical technique (bicaval vs biatrial) right‐sided AA was most common. Acute success occurred in 14/15 (93%) patients and 3/15 (20%) required repeat Abl for recurrence. There were no major complications. Conclusion AA after OHT are most commonly due to atrial macroreentry, but focal arrhythmias and RDC atrial conduction also occur. Ablation of organized AA is usually successful with low risk, warranting early consideration in preference to medical treatment.